Metoda normatywnej rekonstrukcji jako narzędzie krytyki społecznej - Byczyński, Marcin Jan (Filozofia Publiczna i Edukacja Demokratyczna, 2017)
The main objective of this article is to introduce Axel Honneth’s method of normative reconstruction. The stages of its development will be shown—beginning from the intuitive reconstructions of empirically available social normativity up to the perspective of social criticism. Starting with Honneth’s self-criticism towards his own early methodological assumptions, I will indicate relevant factors that influenced the change in his methodological approach. Finally, I shall explain why the criticism formulated against the current stage of Honneth’s theory is mainly inadequate.